Mesenchymal Stem Cells - Isolation, Characterization and Applications 2017
DOI: 10.5772/intechopen.69392
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Full-Term Amniotic Fluid-Derived Mesenchymal Stem Cells in Different Culture Media

Abstract: Amniotic fluid contains precious therapeutic stem cells with ideal features such as they are broadly multipotent, genetically stable, and non-tumorigenic. One of the stem cells that is abundantly found in amniotic fluid is mesenchymal stem cells. Human amniotic fluid mesenchymal stem cells (hAFMSCs) had been successfully isolated from amniotic fluid obtained from second or third trimester amniocentesis. However, studies on hAFMSCs obtained during full-term delivery are still lacking. Furthermore, suitable cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…13 In this study by using flowcytometry technique it has been shown that less then 1% population of Amniotic fluid stem cells (CD117 + cells) were present in the samples which were characterized by using antibodies against cell surface marker, for further conformation we also used negative marker CD34, which were not detected in amniotic fluid. 14 At stage of nephron progenitor cells it is very important to express the protein at molecular level, which we confirmed using Immunofluorescence, the one positive marker (WT1). 15 One negative marker (CD117), and secondary antibodies used as isotype control.…”
Section: Discussionsupporting
confidence: 65%
“…13 In this study by using flowcytometry technique it has been shown that less then 1% population of Amniotic fluid stem cells (CD117 + cells) were present in the samples which were characterized by using antibodies against cell surface marker, for further conformation we also used negative marker CD34, which were not detected in amniotic fluid. 14 At stage of nephron progenitor cells it is very important to express the protein at molecular level, which we confirmed using Immunofluorescence, the one positive marker (WT1). 15 One negative marker (CD117), and secondary antibodies used as isotype control.…”
Section: Discussionsupporting
confidence: 65%
“…Only small number of positive cells was present in amniotic fluid which as reported in previous studies. 12 Phase contrast microscopy revealed that, first AFSCs were appeared as spindle shaped and later it showed as round clusters (resembling NPCs) as mentioned in various studies. [13][14][15][16][17][18] In present study, confirmation of nephron progenitor cells was done by WT1 antibody which is highly expressive in NPCs, whereas in prior studies, SIX2 was also expressed along with WT1.…”
Section: Resultsmentioning
confidence: 63%
“…Amniotic liquid is still considered an important source of MSC for cell-based therapy [ 33 ]. AF-MSC have been largely described and fulfilling all the criteria needed (surface markers and gene expressions) to be defined as multipotent MSC [ 34 , 35 , 36 ]. AF-MSCs are accessible and easily isolated/purified in a less invasive manner than other extraembryonic and somatic MSCs.…”
Section: Extraembryonic Mscmentioning
confidence: 99%